THE INFLUENCE OF THE STRUCTURAL ANALYTICAL METHOD (SAS) WITH THE ASSISTANCE OF BIG BOOK MEDIA ON ELEMENTARY SCHOOL STUDENTS' BEGINNING READING ABILITY - Windiarum, Windy Hikmah Pambudiani; Amelia, Decenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research was motivated by the results of UNESCO and PISA which stated that the literacy rate in Indonesia is still low, especially in beginning reading in elementary school students. The purpose of this study was to measure the initial reading ability of elementary school students, especially in grade I students. This research is a quasi-experimental research with a quantitative approach. Sampling was carried out using purposive sampling techniques. In obtaining data, researchers conducted initial tests (pretest) and final tests (posttest) in the form of preliminary reading tests, observation sheets and interviews. The data technique used is to use descriptive analysis techniques and descriptive statistical analysis by testing hypotheses using t-test statistics.. The data obtained are then analyzed using statistical analysis techniques, namely descriptive statistics. Descriptive statistical analysis data obtained average value (pretest) = 69,17 is in the very low category and average value (posttest) = 83,00 is in the high category. From the results of the hypothesis test analysis using paired sample test, a sig value = 0,001 is obtained in accordance with the basis for decision making, if the hypothesis test of the probability value of significance < 0.05, then H0 is rejected and Ha is accepted. Then significantly the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Based on the hypothesis test, it can be concluded that the synthetic analytical structural method (SAS) with the help of big book media affects the initial reading ability in grade I students of SDN Kebalen 01 Kabupaten Bekasi.